Multi-body simulation of an ankle foot orthosis mechanics - Steck, Patrick; Scherb, David; Miehling, Jörg; Wartzack, Sandro (Proceedings from the NAFEMS DACH Conference 2024, 2024)
In Germany, more than 200,000 first strokes and over 70,000 recurrent strokes occur every year. A stroke often leads to damage to the central nervous system, which is responsible for signal transmission and processing between the brain and muscles, among other things. This results in disorders of the musculoskeletal system, which in turn can lead to pathophysiological movement. In this case, the maximum forces exerted by the lower leg muscles are reduced. A mechanical concept for a passive ankle orthosis is currently being developed at the KTmfk, which help to support the complete gait cycle of patients in the future. Initially, movement data was collected from healthy test subjects. The human model simulation software OpenSim was then used to determine the support curves required by the ankle orthosis for patients with various states of weakness. These sequences were then imported into Ansys Motion in order to simulate the various switching processes within the mechanism during the entire gait cycle. During a gait phase (e.g. roll-off phase), a resulting displacement is calculated, which leads to an increase in the energy stored in the orthosis. This in turn can be released in other gait phases (e.g. the push-off phase) and thus provide a corresponding support force. The temporal sequence of the release moments was integrated into an Ansys Workbench and the resulting signals were passed on to linked components. Various design points were then initialized at which optimal energy storage can be calculated using torsion springs. The parameter optimization of the components relevant for energy storage runs parallel to other musculoskeletal simulations and ultimately ensures support adapted to the patient.<br
Keywords: Mulit-Body Simulation; Orthoses; Design for Medical Devices; AFO; Conceptual Design